Oral treatment with Rosa multiflora fructus extract modulates mast cells in canine atopic dermatitis - Shin, Ha-Young; Shin, Sang Hun; Shin, Hee Soon; Tae, Hyun-Jin; Kim, Hyun-Jin; Hwang, Jeong Ho (Frontiers in Veterinary Science, 2025)
IntroductionCanine atopic dermatitis is a hereditary, often pruritic, and predominantly T-cell-driven inflammatory skin disease involving an interplay between skin barrier abnormalities and allergen sensitization. However, progress in developing therapeutics for companion animals remains slow, with few drugs advancing to Phase II clinical trials to investigate the underlying mechanisms in target animals. While Rosa multiflora fruit extract (RMFE) has been strongly implicated in the improvement of various inflammatory diseases, its effects on canine atopic dermatitis (cAD) and the putative underlying mechanisms remain unclear. In this study, we aimed to evaluate the efficacy of RMFE in the treatment of cAD and explore its underlying mechanisms.MethodsIn this study, RMFE was administered orally (repeatedly for 2 weeks) to ovalbumin (OVA)-induced atopic dermatitis-induced beagles. The effects of RMFE on cAD were assessed through clinical symptom observation and scoring using the canine atopic dermatitis extent and severity index. Additionally, histopathological analysis was performed (hematoxylin and eosin, Masson’s trichrome, and toluidine blue). Cluster of differentiation 4-positive immunostaining was also performed, along with cytokine level and messenger ribonucleic acid level analyses of T-helper 2 (Th2) immune and inflammatory response markers in the modeled skin.ResultsRMFE improved the clinical manifestations of cAD, leading to histopathological modulation of inflammation and immune cells. It also altered Th2 effector cytokine levels. Furthermore, RMFE reduced allergic responses in the AD model dogs by reducing mast cell numbers, inhibiting their activation to release inflammatory mediators, and reducing immunoglobulin E (IgE) production.DiscussionOur results suggest that RMFE can modulate mast cell activation and Th2-dominant immune responses in cAD, helping to reduce AD-induced inflammatory responses.